AN EMPIRICAL EXAMINATION OF PATENT HOLDUP. (20th August 2015) - Galetovic, Alexander; Haber, Stephen; Levine, Ross
Abstract : A large theoretical literature asserts that standard-essential patents (SEPs) allow their owners to "hold up" innovation by charging fees that exceed their incremental contribution to a final product. We evaluate two central, interrelated predictions of this SEP holdup hypothesis: (1) SEP-reliant industries should experience more stagnant quality-adjusted prices than non-SEP-reliant industries; and (2) court decisions that reduce the excessive power of SEP holders should accelerate innovation in SEP-reliant industries. We find no empirical support for either prediction. Indeed, SEP-reliant industries have the fastest quality-adjusted price declines in the U.S. economy.